Penerapan Prinsip Kehati-Hatian Terhadap Tanggung Jawab Notaris Dan Ppat Dalam Hal Terjadi Sertifikat Ganda Dalam Proses Balik Nama - Kresna Yahya (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The Notary profession has a very important position in every legal document regarding its legality. Notaries have a crucial role in various letters, documents, certificates, which become absolute evidence in proof. This causes the authority of the Notary to be guided by the principle of prudence in carrying out its responsibilities to avoid parties being harmed as a result of the exercise of this authority. However, it is not uncommon for Notaries to encounter legal problems when exercising their authority, for example, the existence of multiple certificates when transferring names. To deal with this legal problem, the Notary has the responsibility to ensure the validity and legality of each of these certificates to be able to reverse the name based on the principle of prudence. This research is a normative juridical research using 2 (two) approach methods, namely statutory approach and conceptual approach. The result of this research is that the application of the precautionary principle by Notary in the event of multiple certificates in the name change process can be implemented through Notary's action to conduct a thorough verification of juridical and physical land data through the land information system and postpone the name change process until the Court decides / determines the validity and legality of each certificate between the disputing parties.